Case Report: Three cases of clinically suspected viral myocarditis with recovery of left ventricular dysfunction - Brown, Jonathan; Rashid, Hytham; Sarva, Siva T.; Tatapudi, Suhas; Kalathoor, Jeby; Srinivasan, Aswin; Daniel, Michael; Raza, Syed (Frontiers in Cardiovascular Medicine, 2024)
Viral myocarditis is an important cause of non-ischemic cardiomyopathy. Multiple clinical manifestations have been reported, including acute heart failure, cardiogenic shock, and ventricular arrhythmias. We present three patients with clinically suspected viral myocarditis causing acute heart failure. Serum coxsackievirus B antibodies were positive in all three patients. Each case resulted in significant clinical improvement with hemodynamic support and acute recovery of left ventricular ejection fraction. Despite an initial critical presentation concerning for cardiogenic shock, we highlight three cases of clinically suspected coxsackie myocarditis with an excellent short-term prognosis.